Effect of crystal pre-straining on phonon damping of dislocations - Petchenko, A.M.; Petchenko, G.A. (Functional Materials, 2008)
The damped dislocation resonance in KBr crystals at 0.75 % residual strain has been studied in the 77 to 300 K temperature range using the pulsed echo technique. The sample strain change has been found to influence considerably the dislocation resonance localization but does not affect the absolute value of viscosity coefficient B and its temperature dependence. Basing on the frequency spectra and temperature dependences of other quantities, the temperature-dependent variations of the dislocation damping factor, B, and the average effective length of the dislocation segment, L, were determined within the mentioned temperature range. The dislocation fixation process in the crystals at 0. 75 % residual strain at temperature lowering has been found to be controlled by the simultaneous action of weak and strong stoppers. Comparing the experimental B(T) dependence with theoretical curve calculated using the Alshits-Indenbom theory, it has been established that the viscous dislocation damping in KBr crystals is limited by superposition of phonon wind and "slow" phonon relaxation mechanisms. Імпульсним луна-методом досліджено задемпфований дислокаційний резонанс у кристалах KBr із залишковою деформацією 0,75 % у температурному інтервалі 77-300 К. Виявлено, що зміна деформації зразка істотно впливає на локалізацію дислокаційного резонансу, однак не позначається на абсолютній величині коефіцієнта в'язкості В і його температурному ході. 3 аналізу частотних спектрів і температурного ходу інших величин визначено температурні зміни коефіцієнта демпфування дислокацій В і середньої ефективної довжини дислокаційного сегмента L у вказаному інтервалі температур. Виявлено, що процес закріплення дислокацій у кристалах із залишковою деформацією 0,75 % при зниженні температури контролюється одночасною дією слабких і сильних стопорів. 'У результаті порівняння експериментальної залежності В(Т) і теоретичної кривої, обчисленої за теорією Альшиця-Інденбома, встановлено, що в'язке гальмування дислокацій у кристалах KBr лімітується суперпозицією механізмів фононного вітру і релаксації "повільних" фононів. Импульсным эхо-методом исследован задемпфированный дислокационный резонанс в кристаллах KBr с остаточной деформацией 0,75 % в температурном интервале 77-300 К. Обнаружено, что изменение деформации образца существенно влияет на локализацию дислокационного резонанса, однако не сказывается на абсолютной величине коэффициента вязкости В и его температурном ходе. Из анализа частотных спектров и температурного хода других величин определены температурные изменения коэффициента демпфирования дислокаций В и средней эффективной длины дислокационного сегмента L в указанном интервале температур. Выявлено, что процесс закрепления дислокаций в кристаллах с остаточной деформацией 0,75 % при снижении температуры контролируется одновременным действием слабых и сильных стопоров. В результате сравнения экспериментальной зависимости В(Т) с теоретической кривой, вычисленной по теории Альшица-Инденбома, установлено, что вязкое торможение дислокаций в кристаллах KBr лимитируется суперпозицией механизмов фононного ветра и релаксации "медленных" фононов.